The Correlation of Soft Skills and Hard Skills to Learning Outcomes of Mathematics Students - Dini Palupi Putri (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
The goal of the 2013 curriculum is to develop the next generation of citizens who have positive personality traits, can contribute to social life, and can compete in life in the future. It necessitates not just hard skills but also soft skills, which the future generation must acquire. The purpose of this research is to examine the link between students' soft skills and hard talents. The research method is employed in quantitative research. This study's sample consists of Mathematics Education students for the 2019/2020 school year. Questionnaires and tests are employed as tools. According to the questionnaire data, the soft skills of the Mathematics Education Study Program students at IAIN Curup were in a good category, namely 53.125 percent. The hard skills of the Mathematics Education Study Program students at IAIN Curup were also in a good category, namely 50 percent. According to the hypothesis test, there is no link between students' soft skills and hard skills to learning outcomes. Students' soft skills development may be applied to activities both inside and outside of the classroom and an integrated curriculum that includes both hard skills and soft skills. Student involvement in groups with practical activities is critical to enhancing adaptability, teamwork, tolerance, discipline, and responsibility.